Student Errors in Solving System of Linear Inequalities Story Questions Based on Newman’s Error Analysis (NEA) - Purmanna, Astrino; Raharjo, Sigit (Universitas Teknokrat Indonesia, 2024)
This paper aims to describe the types of error and the causes of student error in solve math story questions on the subject matter of systems of linear inequalities based on Newman's Error Analysis (NEA). The linear inequalities system material was chosen for this study because the linear inequalities system has components that students must understand so they can easily determine the error made by student. This study is a qualitative descriptive. The subjects of this study were taken using a purposive sampling technique and obtained 10 students in the 5th semester of math education study program, Muhammadiyah University of Tangerang. This research was divided into three stage, namely the preparation of research instrument, implementation and colection of data study and data analysis. The instrument used in this research is a description of 3 questions. Based on data analysis, the factor that led to student error in solve math story question on the subject matter of the system of linear inequalities based on NEA were inaccurate, unable to read questions, unable to understand the question, and unable to carry out procedure or steps that would used to problem solving. This study contributes to providing information on errors that are commonly made by student in solve math story questions on the subject matter system linear inequalities based on NEA.